2016
DOI: 10.3389/fnmol.2016.00141
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Interhemispheric Functional Connectivity Rather than Structural Connectivity in Irritable Bowel Syndrome

Abstract: Neuroimaging studies have demonstrated that irritable bowel syndrome (IBS)—a relapsing functional bowel disorder—presents with disrupted brain connections. However, little is known about the alterations of interhemispheric functional connectivity and underlying structural connectivity in IBS. This study combined resting-state functional magnetic resonance imaging (rs-fMRI) and diffusion tensor imaging (DTI) to investigate changes in interhemispheric coordination in IBS patients. Resting-state functional and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Although our study findings point to decreased FA in the right dorsal cingulum in young IBS patients compared to matched healthy controls, the pathogenesis underlying these WM changes cannot be discerned from the present data. WM abnormalities in FA and other non-FA metrics in the cingulum have been linked to anxiety disorders such generalized anxiety disorder, obsessive-compulsive disorder and post-traumatic stress disorder ( Lochner et al, 2012 ; Daniels et al, 2013 ; Wang et al, 2016 ), as well a various pain conditions, including complex regional pain syndrome (CRPS), temporomandibular disorder, chronic musculoskeletal pain, trigeminal neuralgia, and IBS ( Geha et al, 2008 ; Chen et al, 2011 ; Moayedi et al, 2012 ; Ellingson et al, 2013 ; DeSouza et al, 2014 ; Lieberman et al, 2014 ; Qi et al, 2016 ). Therefore, it is possible that the observed microstructural WM changes reflect sensitization of viscerosomatic nociceptive afferents, leading to functional reorganization in spinothalamic and corticolimbic tracts involved in processing pain and affect, including the dorsal cingulum bundle.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study findings point to decreased FA in the right dorsal cingulum in young IBS patients compared to matched healthy controls, the pathogenesis underlying these WM changes cannot be discerned from the present data. WM abnormalities in FA and other non-FA metrics in the cingulum have been linked to anxiety disorders such generalized anxiety disorder, obsessive-compulsive disorder and post-traumatic stress disorder ( Lochner et al, 2012 ; Daniels et al, 2013 ; Wang et al, 2016 ), as well a various pain conditions, including complex regional pain syndrome (CRPS), temporomandibular disorder, chronic musculoskeletal pain, trigeminal neuralgia, and IBS ( Geha et al, 2008 ; Chen et al, 2011 ; Moayedi et al, 2012 ; Ellingson et al, 2013 ; DeSouza et al, 2014 ; Lieberman et al, 2014 ; Qi et al, 2016 ). Therefore, it is possible that the observed microstructural WM changes reflect sensitization of viscerosomatic nociceptive afferents, leading to functional reorganization in spinothalamic and corticolimbic tracts involved in processing pain and affect, including the dorsal cingulum bundle.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, brain regions with high intensity show high VMHC values. VMHC can quantize FC between every voxel in two hemispheres and has been applied more and more extensively in the area of pathergasiology (Liang et al, 2017; Qi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the SII, functional coupling was also observed between the pIns in the right hemisphere and BG and aIns in the opposite hemisphere. Activity of the BG and insula is strongly synchronized between the hemispheres through the anterior commissure and/or corpus callosum (O’Reilly et al, 2013; Sun et al, 2015; Qi et al, 2016; Su et al, 2016). This may explain why the pIns increased functional connectivity with the BG and aIns not only in the same hemisphere but also opposite hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…However, though it did not reach our cluster size threshold, two regions in the right BG showed that intensity of functional connectivity with the right pIns had negative correlation with itch NRS (at least significant for intensity threshold for both regions). Considering strong interhemispheric connectivity of the BG (O’Reilly et al, 2013; Qi et al, 2016), functional network composed of the pIns and bilateral BG may play an important role in regulation of subjective itch sensation.…”
Section: Discussionmentioning
confidence: 99%